P113 Comparative invasiveness of assisted reproductive techniques: A preliminary study - Y. Serrano; F. Bennett; J.R. Crabtree (Journal of Equine Veterinary Science, 2026)

Genetic variation and race structure in the tan spot wheat pathogen Pyrenophora tritici-repentis: a microscale assessment in a wheat field of Western Australia - Pao Theen See; Catherine F. Cupitt; Dion Bennett; Caroline S. Moffat; Simon R. Ellwood (Australasian Plant Pathology, 2026)
Population genetics are routinely studied over vast geographical areas to address questions of origin, routes of migration and epidemiology. However, genetic diversity of certain microorganisms such as plant pathogenic fungi are difficult to study even on a small geographical scale due to their mixed reproduction systems, variable population sizes, clonality and versatility to host adaptation. The genetic variation of an economically important wheat fungal pathogen, Pyrenophora tritici-repentis (Ptr), was studied with isolates collected from a naturally infected wheat field located in Western Australia, using microsatellite (SSR) markers. Out of 142 Ptr isolates, 89 individuals showed unique multilocus haplotypes. On single leaves, individual disease lesions mostly consisted of genetically variable Ptr isolates, with very few clonal isolates. Distribution analysis of these indicated that wind-dispersal of Ptr conidia occurred over a small scale within individual leaves as well as longer dispersions of up to 45 m. Race evaluation of the population via effector gene PCR assays defined 136 isolates as race 1 and six as race 2, and there was no indication of genetic groupings based on micro-locations or race. Population structure analysis suggests that the population consists of mixed migrants from long wind-dispersal or field management activities. Nucleotide sequence analysis of the homothallic mating-type genes, MAT1-1 and MAT1-2 revealed sequence conservation within the population. Altogether, the microscale evaluation of the single wheat field isolates demonstrated that the population is suitable for disease screening as it is representative of the wider Ptr population demographic in Australia.

Soil fungal communities differ among forest types but show limited response to cessation of ecosystem engineering by the superb Lyrebird (Menura novaehollandiae) - Alex C. Maisey; Lucie Semenec; Eleonora Egidi; Angie Haslem; Andrew F. Bennett (Fungal Ecology, 2026)

Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

Novel symbioses between reef fishes and serpulid polychaetes in the Caribbean Sea - Morgan F. Bennett-Smith; Elizabeth McNamee; Samantha Masih; Timothy Lis; Mason Murchison; Allison Cinelli; Toshith Bhaumik; Catheline Y. M. Froehlich; Anna DeLoach; Ned DeLoach; Ninon Martinez; Peter M. Buston; et al. (Symbiosis, 2026)

Corporations and financial institutions driving coastal conflicts involving Indigenous Peoples - Sebastian Villasante; Julia Tovar Verba; Veronica Relano; Sílvia Gómez; José Bakit; Nathan J. Bennett; Anthony Charles; Rafael Calderón-Contreras; Andrés M. Cisneros-Montemayor; Bernardo M. Flores; Lucas A. Garibaldi; Maria Grazia Pennino; et al. (Ambio, 2026)
Socio-environmental conflicts associated with large-scale economic projects in Indigenous territories are well documented, but conflicts in coastal areas remain largely unexplored, despite the crucial differences between inland and coastal ecosystems. While the empirical literature about socio-environmental conflicts in Indigenous territories in coastal areas is growing, the role of financial institutions and corporations in these conflicts is often overlooked. This study addresses this gap by examining the financial institutions and corporations associated with more than 400 reported socio-environmental conflicts affecting Indigenous Peoples in coastal areas worldwide. Our results show that most financial institutions supporting projects linked to conflicts are based in West Europe and North America, with North American financial institutions linked to multiple projects. The energy sector accounts for the highest number of socio-environmental conflicts, particularly those involving corporations operating across continents. Many European and North American corporations operate mostly in Africa, but also globally. Corporations with overseas operations are associated with a higher intensity of conflicts. These findings highlight the need to scrutinize financial investments and corporate practices driving socio-environmental conflicts in coastal Indigenous territories, where human rights are often at risk. The lack of due diligence and accountability in applying environmental and social safeguards weakens protections for both ecosystems and Indigenous communities. Strengthening the enforcement of national and international laws on environmental sustainability, human rights and Indigenous rights is therefore essential for coastal development projects.

Omega-3 PUFA concentration and emulsification govern lipid digestion, micellar vesicle formation, and oral bioavailability of fish oil concentrates - Amer Abdelhafez; Zahra Khabir; Alfonso Garcia-Bennett; Clive A. Prestidge; Fabrizio F. Camponovo; Paul Joyce (Food Bioscience, 2026)

Lung cancer risk in relation to indicative radon atlas metrics in Northern Ireland: a population-based case–control study using secondary data - Claire M. Delargy; Helen G. Coleman; Quentin G. Crowley; Damien Bennett; Javier Elio; Deirdre Fitzpatrick; Helen Mitchell; Sara M. Wallace; Rawan A. N. Alhattab; Angela Scott; Bernadette McGuinness; Ruth F. Hunter; et al. (Environmental Geochemistry and Health, 2026)
Radon is an established lung carcinogen, but more research is needed to inform whether area-based measures of radon exposure reflect underlying cancer risk. This study, the first of its kind in the UK, aimed to investigate the association between a nationwide indicative radon atlas and lung cancer risk in Northern Ireland, a region in which lung cancer screening programmes are under design. A population-based case–control study was conducted. Primary lung cancer cases ( n = 1,687) from the Northern Ireland Cancer Registry diagnosed in 2006 and 2014 were compared with 8,094 non-lung cancer controls from a large cohort. Radon exposure data were extracted from the Indicative Atlas of Radon, which categorises 1 km 2 areas by the percentage of households exceeding 200 Bq/m 3 . Exposure data were linked to participants by postcode. Logistic regression models adjusted for age, sex, smoking status, deprivation and PM 2.5 exposure were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for lung cancer. Individuals residing in high radon exposure areas (Atlas Class 6) had a greater than two-fold lung cancer risk (adjusted OR: 2.24, 95% CI: 1.25, 3.92) compared to residents in all other areas. This association was revealed after adjusting for PM 2.5 . This study supports the utility of an indicative radon atlas in reflecting underlying population lung cancer risk associated with radon, while highlighting constraints inherent to atlas-based exposure classification and secondary data.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Effects of selected food-compatible printing materials on product properties towards 3D binder jetting - Dang Chung Nguyen; Rico F. Tabor; Yunlong Tang; Louise Bennett; Shahnaz Mansouri (Journal of Food Engineering, 2026)

Bomb radiocarbon reveals keratin growth dynamics in loggerhead (Caretta caretta) and green (Chelonia mydas) turtles - Bethan Linscott; Amy A. Wallace; Lorena Becerra-Valdivia; Matt R. P. Harris; Alexandra L. Fireman; Jenna D. Bennett; William F. Patterson; Hannah B. Vander Zanden (Marine Biology, 2026)
Incrementally formed biological tissues can serve as archives of biochemical information pertaining to the life histories of organisms. The sequential isotopic analysis of marine turtle scute keratin is increasingly used for ecological reconstruction, but the timescales represented by these tissues remain poorly understood. Here, we present a method to establish scute growth rates using sequential radiocarbon ( 14 C) measurements on samples taken from loggerhead ( Caretta caretta ) and green turtles ( Chelonia mydas ) stranded along the Florida coast. Using a Δ 14 C coral-otolith reference series and a Bayesian modelling approach, we reconstructed the rate of keratin formation in 24 individuals (representing 120 radiocarbon measurements) and detected synchronous declines in scute growth rates that may be linked to marine environmental stress. Our results provide a chronological framework for the ecological interpretation of biogeochemical data from green and loggerhead turtle scutes and demonstrate the potential for 14 C analysis to investigate the growth dynamics of other incremental tissues.

Gaps in tipping points research across freshwater, marine, and terrestrial ecosystems - Meagan Harper; Charlotte Carrier-Belleau; Trina Rytwinski; Brian Helmuth; Irena F. Creed; John P. Smol; Joseph R. Bennett; Dalal E.L. Hanna; Leonardo A. Saravia; Juan Rocha; Aubrey Foulk; Sam Dupont; et al. (Biological Conservation, 2026)

Appearance Pressure From the Media Mediates the Relationship Between Internalized Weight Bias and Eating Disorder Risk for Young Women: A Cross-Sectional Study - Brooke L. Bennett; Allison F. Wagner; Rachel D. Marshall; Janet D. Latner (Journal of the Academy of Nutrition and Dietetics, 2025)

Reducing non-revenue water in peri-urban Tanzania through an integrated data-driven approach: a pilot study in Dodoma - M. M. Kwikima; G. Bennett; F. K. Ahmada; A. Magina (International Journal of Energy and Water Resources, 2025)

Accelerating biotherapeutics discovery: Blueprint for a universal LC-MALDI-MS offline approach - Elizabeth F. Bayne; Xiong-Zhuo Gao; Yuan Jiang; Raffeal Bennett; Erik L. Regalado; Gregory F. Pirrone; Alexey A. Makarov (Analytica Chimica Acta, 2025)

Recent Results on Science and Innovation Related to Electrical Processes of Thunderstorms - Christoph Köhn; Torsten Neubert; Martin Füllekrug; Ute Ebert; Sander Nijdam; Olivier Chanrion; Nikolai Østgaard; Martino Marisaldi; Serge Soula; Joan Montanyà; Francisco Gordillo-Vázquez; Alejandro Luque; et al. (Surveys in Geophysics, 2025)

Towards identifying the economically optimum sampling density for variable-rate soil constraint management - S. D. Roberton; J. McL. Bennett; C. R. Lobsey; T. F. A. Bishop (Precision Agriculture, 2025)
The investment in soil sampling is often disproportionate to the level of investment for soil amelioration. While advanced geostatistical Digital Soil Mapping (DSM) methods exist to map spatially variable soils, they are rarely used in precision agriculture, due to the increased soil sampling requirement, the cost of which is perceived as prohibitive. Consequently, soil constraints are regularly managed on blanket-rate basis, where a single rate is applied across spatial variable soils. What sampling density is required to deploy these methods in practice, and can an increased investment in soil sampling enable more economically optimised soil amelioration? This paper presents a method to answer this question in Australian broadacre agriculture. The method, which seeks to identify the economically optimum sampling density, is tested on a 100 ha broadacre grain field in Central NSW, Australia. Sampling densities ranging from 0.1 to 3 samples per ha are tested, through observing the accuracy of gypsum recommendations as a practice to treat sodic soils. A status quo Blanket-rate (BR) approach is tested against DSM via the deployment of ordinary kriging to create continuous variable-rate (VR) recommendations. Application errors are assessed both in terms of cost of over-applied product, as well as lost yield potentialy due to under-application. While for this test site, an economically optimum sampling density of 1 core per 5 ha and 1 core per 2 ha for 0–20 cm topsoil management and 0–60 cm profile management was identified, we propose the development Nopt function. Development of this function would allow for optimum sampling investments to be estimated at new sites, in consideration to the inherent site variability and the economic magnitude of soil amelioration. Through development of this function and it’s applied example in this paper, we seek to develop the value proposition for increased soil data collection in Australian Agriculture.

New records of fishes from the Coral Sea Marine Park, Australia - Yi-Kai Tea; Tiffany L. Sih; Fenton Walsh; Timothy Bennett; Luiz A. Rocha; Ghislain Bardout; Amanda Hay; Kerryn Parkinson; Sally Reader; Indiana J. Riley; John J. Pogonoski; Jeffrey W. Johnson; et al. (Coral Reefs, 2025)
With an area covering just under 1 million km 2 , Australia’s Coral Sea Marine Park (CSMP) is among the largest marine protected areas globally. Yet, the demersal deep-reef fish fauna of the CSMP remains poorly described, due in part to its remote location, as well as its sheer size, much of which is inaccessible below conventional SCUBA diving depths. Recent remotely operated vehicle (ROV) explorations conducted by the Schmidt Ocean Institute provided an opportunity to explore the benthic ichthyofauna of deep mesophotic and rariphotic coral ecosystems. Contributions to the deep, demersal ichthyofauna of Australia’s CSMP are herein supplemented with an integrative dataset consisting of ROV imagery and specimen vouchers. Sixty-two new records of fishes from 26 families are reported from the CSMP. Of these, 45 are new Australian records, one of which is also a new family record for Australia. Four species are new records for the Southern Hemisphere, and 21 species are potentially new to science. We report new voucher material for 29 species, including several species previously identified as new for the CSMP with no voucher specimens.

A Framework for Modelling Thermal Load Sensitivity Across Life - Pieter A. Arnold; Daniel W. A. Noble; Adrienne B. Nicotra; Michael R. Kearney; Enrico L. Rezende; Samuel C. Andrew; Verónica F. Briceño; Lauren B. Buckley; Keith A. Christian; Susana Clusella‐Trullas; Sonya R. Geange; Lydia K. Guja; et al. (Global Change Biology, 2025)
Forecasts of vulnerability to climate warming require an integrative understanding of how species are exposed to, are damaged by, and recover from thermal stress in natural environments. The sensitivity of species to temperature depends on the frequency, duration, and magnitude of thermal stress. Thus, there is a generally recognized need to move beyond physiological metrics based solely on critical thermal limits and integrate them with natural heat exposure regimes. Here we propose the thermal load sensitivity (TLS) framework, which integrates biophysical principles for quantifying exposure with physiological principles of the dynamics of damage and repair processes in driving sublethal impacts on organisms. Building upon the established thermal death time (TDT) model, which integrates both the magnitude and duration of stress, the TLS framework attempts to disentangle the accumulation of damage and subsequent repair processes that alter responses to thermal stress. With the aid of case studies and reproducible simulation examples, we discuss how the TLS framework can be applied to enhance our understanding of the ecology and evolution of heat stress responses. These include assessing thermal sensitivity across diverse taxonomic groups, throughout ontogeny, and for modular organisms, as well as integrating additional stressors in combination with temperature. We identify critical research opportunities, knowledge gaps, and novel ways of integrating physiological measures of thermal sensitivity to improve understanding and predictions of thermal vulnerability at various scales across life.

Evidence of novel symbiotic relationships between Christmas tree worms and coral reef blennies and gobies - Morgan F. Bennett-Smith; Catheline Y.M. Froehlich; Lili F. Vizer; Peter M. Buston (Symbiosis, 2025)

Latitudinal gradients in herbivorous and detritivorous reef fish productivity - Sterling B. Tebbett; Helen F. Yan; Scott Bennett; Graham J. Edgar; Scott D. Ling; Rick D. Stuart-Smith; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Novel Curvularia species causing disseminated phaeohyphomycosis in a dog - Jared A. Jaffey; Connie F. Cañete-Gibas; Nathan P. Wiederhold; Carmita J. Sanders; Jason D. Struthers; Annalise Black; BinXi Wu; Kara S. Thomas; Patricia Bennett; Jessica Watt (Topics in Companion Animal Medicine, 2025)

Biodiversity accounting on farms: Relating diversity of bird assemblages to ecosystem condition - Frederick W. Rainsford; Alex Maisey; Daniel O'Brien; Sue Ogilvy; William F. Mitchell; Andrew F. Bennett; James Q. Radford (Science of The Total Environment, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Analysis of the Atomistic MD Simulations of CI+CIII2 Interactions and Associated Lipid Binding - Amina Djurabekova; Young-Cheul Shin; Pedro Latorre-Muro; Oleksii Zdorevskyi; Christopher F. Bennett; Nils Burger; Kangkang Song; Chen Xu; Maofu Liao; Pere Puigserver; Vivek Sharma (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Emotional and functional well-being in long-term breast cancer survivorship - Yumeng Ren; Joanna Maselko; Xianming Tan; Andrew F. Olshan; Angela M. Stover; Antonia V. Bennett; Katherine E. Reeder-Hayes; Jessie K. Edwards; Bryce B. Reeve; Melissa A. Troester; Marc A. Emerson (Cancer Causes & Control, 2024)

The noisy neighbor conundrum: what influences the value of urban sites for forest birds? - Jacinta E. Humphrey; Angie Haslem; Andrew F. Bennett (Urban Ecosystems, 2024)

Imaging Sonar Reveals Diel Movement of Fish Throughout a Developed Australian Estuary - Kristen L. McSpadden; Vincent Raoult; Mark A. Bennett; Troy F. Gaston (Estuaries and Coasts, 2024)

The future of gender research in small‐scale fisheries: Priorities and pathways for advancing gender equity - Emma D. Rice; Edith Gondwe; Abigail E. Bennett; Patrick Asango Okanga; Nimah F. Osho‐Abdulgafar; Kafayat Fakoya; Ayodele Oloko; Sarah Harper; Patrick Chimseu Kawaye; Ernest O. Chuku; Hillary Smith (Fish and Fisheries, 2024)
This paper presents an agenda for the future of gender research in small‐scale fisheries (SSF). Building on expert insight from scholars who gathered during the 4th World Small‐Scale Fisheries Congress Africa (4WSFC) with a synthesis of existing literature, we identify six topics that warrant future investigation in SSF, along with methodological considerations for addressing them. Research priorities include identifying pathways towards (1) equitable participation in governance and decision‐making, (2) valuing all actors' contributions to aquatic food systems, (3) increasing access to financial services, (4) inclusive infrastructural development, (5) livelihood diversification and (6) reducing occupational health hazards. Several important methodological considerations include (i) using multiple methodologies, (ii) applying participatory methods, (iii) collecting gender‐disaggregated data, (iv) integrating gender into a food systems approach in fisheries, (v) engaging an intersectional approach and (vi) operationalising equity.

Structured decision making remains underused in ecological restoration despite opportunities - Morgan L. Piczak; Jessica A. Robichaud; Peter Morrison; Andrew M. Rous; Ingeborg M. Mulder; Cassandra J. Hill; Tanya S. Prystay; Hanna Rosner-Katz; Kelly F. Robinson; Joseph R. Bennett; Steven J. Cooke (Environment Systems and Decisions, 2024)

Unconfined fishway design, implementation, and assessment for the emerald Shiner (Notropis atherinoides) in the Upper Niagara River, New York - Jundong Qiao; Sean J. Bennett; Joseph F. Atkinson; Paul A. Cocca; Sarah K. Delavan; Andrew R. Hannes; Bryan A. Hinterberger; Timothy J. Pede; Alicia Pérez-Fuentetaja; Richard J. Ruby (Ecological Engineering, 2024)

Assessing impacts of a notorious invader (common carp Cyprinus carpio) on Australia's aquatic ecosystems: Coupling abundance-impact relationships with a spatial biomass model - Benjamin G. Fanson; Robin Hale; Jason D. Thiem; Jarod P. Lyon; John D. Koehn; Andrew F. Bennett; Ivor Stuart (Biological Conservation, 2024)

Lithospheric hydrous pyroxenites control localisation and Ni endowment of magmatic sulfide deposits - Isra S. Ezad; Daryl E. Blanks; Stephen F. Foley; David A. Holwell; Jason Bennett; Marco L. Fiorentini (Mineralium Deposita, 2024)

Importance of (semi)natural vegetation on farms for achieving multiple objectives: A conceptual model based on temperate southern Australia - Angie Haslem; Andrew F. Bennett; James Q. Radford (Agricultural Systems, 2024)

Effects of a megafire vary with fire severity and forest type: The impact of Australia's ‘Black Summer’ fires on the superb lyrebird (Menura novaehollandiae), an iconic forest species - Alex C. Maisey; Luke Collins; Graeme Newell; Andrew F. Bennett (Biological Conservation, 2023)

Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

On real estate market transparency: The relationship with ICT trade and investment - Hassan F. Gholipour; Amir Arjomandi; Amirhossein Eslami Andargoli; Rohan Bennett (Land Use Policy, 2023)

Evaluation of Carbon and Nitrogen Stable Isotopes of Red Drum in the Northern Gulf of Mexico - Corbin F. Bennetts; Robert T. Leaf; Kevin S. Dillon (Estuaries and Coasts, 2023)

Valorisation strategies for brown seaweed biomass production in a European context - Joseph P. Bennett; Laura F. Robinson; Leonardo D. Gomez (Algal Research, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

High-resolution patterns and inequalities in ambient fine particle mass (PM2.5) and black carbon (BC) in the Greater Accra Metropolis, Ghana - Abosede S. Alli; Sierra N. Clark; Jiayuan Wang; James Bennett; Allison F. Hughes; Majid Ezzati; Michael Brauer; James Nimo; Josephine Bedford-Moses; Solomon Baah; Alicia Cavanaugh; Samuel Agyei-Mensah; et al. (Science of The Total Environment, 2023)

How expert are ‘experts’? Comparing expert predictions and empirical data on the use of farmland restoration sites by birds - Andrew F. Bennett; Angie Haslem; Matthew White; Tracey Hollings; James R. Thomson (Biological Conservation, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Valorisation of phytochemical from Sitka spruce (Picea sitchensis) needles: Impact of ultrasound/microwave-assisted extraction - Hadil Alaydi; Xianglu Zhu; Julie Rose Mae Mondala; Brijesh K. Tiwari; Bibha Kumari; James F. Curtin; Peter Downey; Michelle McKeon-Bennett; Tanya Beletskaya (Food and Bioproducts Processing, 2023)

Relationships between soil and badger elemental concentrations across a heterogeneously contaminated landscape - Andrea Sartorius; Molly Cahoon; Davide Corbetta; Llorenç Grau-Roma; Matthew F. Johnson; Elsa Sandoval Barron; Matthew Smallman-Raynor; Benjamin M.C. Swift; Lisa Yon; Scott Young; Malcolm Bennett (Science of The Total Environment, 2023)

Quantifying the landscape-scale recovery of bird communities over time in response to on-farm restoration plantings - Angie Haslem; Alex C. Maisey; Rohan H. Clarke; Alistair Stewart; James Q. Radford; Andrew F. Bennett (Biological Conservation, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

High-resolution wave data for improving marine habitat suitability models - Chiara M. Bertelli; William G. Bennett; Harshinie Karunarathna; Dominic E. Reeve; Richard K. F. Unsworth; James C. Bull (Frontiers in Marine Science, 2023)
Habitat suitability modelling (HSM) is a tool that is increasingly being used to help guide decision making for conservation management. It can also be used to focus efforts of restoration in our oceans. To improve on model performance, the best available environmental data along with species distribution data are needed. Marine habitats tend to have ecological niches defined by physical environmental conditions and of particular importance for shallow water species is wave energy. In this study we examined the relative improvements to HSM outputs that could be achieved by producing high-resolution Delft-3D modelled wave height data to see if model predictions at a fine-scale can be improved. Seagrasses were used as an exemplar and comparisons at fine-scale showed considerable differences in the area predicted suitable for seagrass growth and greatly increased the importance of waves as a predictor variable when compared with open-source low resolution wave energy data.

Polymorphism of the follicle stimulating hormone receptor does not impact reproductive performance or in-vitro embryo production in beef heifers - Alexandria P. Snider; Hannah K. Yake; Camryn D. Granger; Shelby L. Rosasco; Tara G. McDaneld; Warren M. Snelling; Chad C. Chase; Jeremy R. Miles; Clay A. Lents; Lacey K. Quail; Jerica J.J. Rich; Kaitlin M. Epperson; et al. (Theriogenology, 2023)

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Incidence and risk factors for respiratory tract bacterial colonization and infection in lung transplant recipients - L. Paglicci; V. Borgo; N. Lanzarone; M. Fabbiani; C. Cassol; MG. Cusi; M. Valassina; S. Scolletta; E. Bargagli; L. Marchetti; P. Paladini; L. Luzzi; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
To evaluate incidence of and risk factors for respiratory bacterial colonization and infections within 30 days from lung transplantation (LT). We retrospectively analyzed microbiological and clinical data from 94 patients transplanted for indications other than cystic fibrosis, focusing on the occurrence of bacterial respiratory colonization or infection during 1 month of follow-up after LT. Thirty-three percent of patients developed lower respiratory bacterial colonization. Bilateral LT and chronic heart diseases were independently associated to a higher risk of overall bacterial colonization. Peptic diseases conferred a higher risk of multi-drug resistant (MDR) colonization, while longer duration of aerosol prophylaxis was associated with a lower risk. Overall, 35% of lung recipients developed bacterial pneumonia. COPD (when compared to idiopathic pulmonary fibrosis, IPF) and higher BMI were associated to a lower risk of bacterial infection. A higher risk of MDR infection was observed in IPF and in patients with pre-transplant colonization and infections. The risk of post-LT respiratory infections could be stratified by considering several factors (indication for LT, type of LT, presence of certain comorbidities, and microbiologic assessment before LT). A wider use of early nebulized therapies could be useful to prevent MDR colonization, thus potentially lowering infectious risk.

A global collaboration to study intimate partner violence-related head trauma: The ENIGMA consortium IPV working group - Carrie Esopenko; Jessica Meyer; Elisabeth A. Wilde; Amy D. Marshall; David F. Tate; Alexander P. Lin; Inga K. Koerte; Kimberly B. Werner; Emily L. Dennis; Ashley L. Ware; Nicola L. de Souza; Deleene S. Menefee; et al. (Brain Imaging and Behavior, 2021)

Assessing the impact of taxon resolution on network structure - David R. Hemprich‐Bennett; Hernani F. M. Oliveira; Steven C. Le Comber; Stephen J. Rossiter; Elizabeth L. Clare (Ecology, 2021)
Constructing ecological networks has become an indispensable approach in understanding how different taxa interact. However, the methods used to generate data in network research vary widely among studies, potentially limiting our ability to compare results meaningfully. In particular, methods of classifying nodes vary in their precision, likely altering the architecture of the network studied. For example, rather than being classified as Linnaean species, taxa are regularly assigned to morphospecies in observational studies, or to molecular operational taxonomic units (MOTUs) in molecular studies, with the latter defined based on an arbitrary threshold of sequence similarity. Although the use of MOTUs in ecological networks holds great potential, especially for allowing rapid construction of large data sets of interactions, it is unclear how the choice of clustering threshold can influence the conclusions obtained. To test the impact of taxonomic precision on network architecture, we obtained and analyzed 16 data sets of ecological interactions, inferred from metabarcoding and observations. Our comparisons of networks constructed under a range of sequence thresholds for assigning taxa demonstrate that even small changes in node resolution can cause wide variation in almost all key metric values. Moreover, relative values of commonly used metrics such as robustness were seen to fluctuate continuously with node resolution, thereby potentially causing error in conclusions drawn when comparing multiple networks. In observational networks, we found that changing node resolution could, in some cases, lead to substantial changes to measurements of network topology. Overall, our findings highlight the importance of classifying nodes to the greatest precision possible, and demonstrate the need for caution when comparing networks that differ with respect to node resolution, even where taxonomic groups and interaction types are similar. In such cases, we recommend that comparisons of networks should focus on relative differences rather than absolute values between the networks studied.

Spatial and temporal patterns of lateralization in a parrot species complex - Mathew L. Berg; Sarah A. Micallef; Justin R. Eastwood; Raoul F. H. Ribot; Andrew T. D. Bennett (Evolutionary Ecology, 2020)

Coral loss alters guarding and farming behavior of a Caribbean damselfish - Valentina Di Santo; Lois A. O’Boyle; Ryan K. Saylor; Theresa F. Dabruzzi; Marthe A. Covell; Katrina Kaack; Rachel Scharer; Katherine Seger; Nicholas Favazza; Christopher M. Pomory; Wayne A. Bennett (Marine Biology, 2020)
Coral loss is a major element of global ecological change in the oceans that may shape the behavior of keystone species such as habitat-attached animals. Farming damselfishes cultivate and aggressively protect algal garden within their territory, thereby shaping local fish assemblages and macro-algae diversity. Following the widespread loss of live branching coral throughout Florida and the Caribbean Sea, dusky damselfish ( Stegastes adustus ) have modified their territorial behavior. We compared antagonistic behavior, and size and algal species composition of territories of dusky damselfish on dead branching coral rubble and live boulder coral in the Dry Tortugas National Park, USA. Even though similar numbers of “intruders” entered each habitat type, dusky damselfish on rubble territories chased out significantly more fishes, had larger territories and more species of algae were present in their gardens. This study shows that dusky damselfish successfully occupy living and dead coral areas; however, there are potential trade-offs between defending a larger territory and cultivating fewer algal species.

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Diverse land-uses shape new bird communities in a changing rural region - Cara E. Sambell; Greg J. Holland; Angie Haslem; Andrew F. Bennett (Biodiversity and Conservation, 2019)

Wildfire refugia in forests: Severe fire weather and drought mute the influence of topography and fuel age - Luke Collins; Andrew F. Bennett; Steve W. J. Leonard; Trent D. Penman (Global Change Biology, 2019)
Wildfire refugia (unburnt patches within large wildfires) are important for the persistence of fire‐sensitive species across forested landscapes globally. A key challenge is to identify the factors that determine the distribution of fire refugia across space and time. In particular, determining the relative influence of climatic and landscape factors is important in order to understand likely changes in the distribution of wildfire refugia under future climates. Here, we examine the relative effect of weather (i.e. fire weather, drought severity) and landscape features (i.e. topography, fuel age, vegetation type) on the occurrence of fire refugia across 26 large wildfires in south‐eastern Australia. Fire weather and drought severity were the primary drivers of the occurrence of fire refugia, moderating the effect of landscape attributes. Unburnt patches rarely occurred under ‘severe’ fire weather, irrespective of drought severity, topography, fuels or vegetation community. The influence of drought severity and landscape factors played out most strongly under ‘moderate’ fire weather. In mesic forests, fire refugia were linked to variables that affect fuel moisture, whereby the occurrence of unburnt patches decreased with increasing drought conditions and were associated with more mesic topographic locations (i.e. gullies, pole‐facing aspects) and vegetation communities (i.e. closed‐forest). In dry forest, the occurrence of refugia was responsive to fuel age, being associated with recently burnt areas (

Integrated Risk Assessment for the Blue Economy - Emma E. Hodgson; Timothy E. Essington; Jameal F. Samhouri; Edward H. Allison; Nathan J. Bennett; Ann Bostrom; Alison C. Cullen; Stephen Kasperski; Phillip S. Levin; Melissa R. Poe (Frontiers in Marine Science, 2019)

Prevalence of BFDV in wild breeding Platycercus elegans - Justin R. Eastwood; Mathew L. Berg; Raoul F. H. Ribot; Katherine L. Buchanan; Ken Walder; Andrew T. D. Bennett (Journal of Ornithology, 2019)

Plumage coloration follows Gloger's rule in a ring species - Raoul F. H. Ribot; Mathew L. Berg; Emanuel Schubert; John A. Endler; Andrew T. D. Bennett (Journal of Biogeography, 2019)
Aim Animal coloration is expected to differ between populations in different habitats according to Gloger's rule, with darker animals found in more humid, vegetated or warmer environments. Yet despite considerable support across the globe, the mechanisms behind this biogeographical rule are currently still unclear. Exploiting a ring species with plumage coloration from crimson to pale yellow, we test Gloger's rule and the mechanisms behind phenotypic divergence. Location South‐eastern Australia. Major taxa studied Crimson rosellas ( Platycercus elegans ). Methods We combined three modelling approaches (spatial regression; random decision forest species distribution and conditional inference tree) to test the association between 10 environmental variables (based on long‐term climate data and remotely sensed reflectance of the land) and plumage coloration across the distribution of P. elegans . We also took in‐situ measurements of background coloration of dominant vegetation to examine the relationship between (a) background coloration measured locally and remotely, (b) P. elegans coloration and (c) known differences in visual sensitivity of the subspecies using species‐specific visual models. Results On both a continental and a local scale, the distribution of yellow‐red plumage coloration was strongly predicted by average rainfall, summer temperature and the Earth's reflectance between 620–670 nm. Remotely sensed radiance measures correlated strongly and positively with reflectance of the leaves of the dominant tree species at sites across the P. elegans distribution. Visual modelling indicated that differences in background colour could affect signalling efficacy in dim‐light conditions. Main conclusions Our study shows that the highly variable plumage coloration conforms to Gloger's rule, and indicates that background coloration of the vegetation and thermoregulation are likely to be important mechanisms. Our results also show that Gloger's rule can explain variation in pigmentary systems other than melanin, and highlight that selection from environmental variation could be an important force behind the geographic diversity found in ring species.

Linear habitats in rural landscapes have complementary roles in bird conservation - Mark Hall; Dale Nimmo; Simon Watson; Andrew F. Bennett (Biodiversity and Conservation, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Flowering and floral visitation predict changes in community structure provided that mycorrhizas remain intact - Jonathan A. Bennett; James F. Cahill (Ecology, 2018)
Pollination is critical for plant fitness and population dynamics, yet little attention is paid to the role of flowering and plant‐pollinator interactions in structuring plant communities, including community responses to environmental change. Changes in arbuscular mycorrhizal fungi ( AMF ), nutrient abundances, and plant litter all affect plant access to different resources, and are known regulators of community structure. Each factor can also affect flowering and plant‐pollinator interactions, potentially contributing to changes in community structure. To test whether AMF , nutrients, and litter influenced the relationship between pollination and community structure, we conducted a 5‐yr field experiment applying fungicide, adding fertilizer, and removing plant litter in native grassland. We measured the distribution of flowers and floral visits among species in year three and linked these measures to changes in plant composition and species richness between years three and five. We hypothesized that an uneven distribution of flowers and visits among species would lead to greater community change, but that the treatments would disrupt this relationship by altering sexual allocation and recruitment. Consistent with our hypothesis, communities with uneven flower distributions exhibited greater changes in community composition and richness under ambient conditions. However, AMF suppression neutralized this relationship and regulated the other treatment effects, highlighting the potential importance of AMF for stabilizing recruitment dynamics. Combined, AMF suppression and nutrient addition caused species losses when few species flowered, likely by compounding stresses for those species. The treatment effects on the relationship between flowering and community composition were more nuanced, but were likely driven by increased competition and altered flowering among species. By contrast, community composition was more stable when visitation rates were uneven among species, irrespective of any treatments. This suggests that some species require high visitation rates to maintain their populations due to greater dependence on sexual reproduction. Combined, these results highlight the importance of flowering and floral visitation to the dynamics of grassland communities. They also suggest that altered recruitment dynamics is a major, yet understudied, mechanism by which environmental change affects communities. Consequently, understanding the effects of environmental change on plant communities will require study of both plant growth and sexual reproduction.

Modulation of near-bed hydrodynamics by freshwater mussels in an experimental channel - Brandon J. Sansom; Joseph F. Atkinson; Sean J. Bennett (Hydrobiologia, 2018)

Exploring UAV in Indonesian cadastral boundary data acquisition - Sheilla Ayu Ramadhani; R. M. Bennett; F. C. Nex (Earth Science Informatics, 2018)

Pineal volume and evening melatonin in young people with affective disorders - Joanne S. Carpenter; Amy C. Abelmann; Sean N. Hatton; Rébecca Robillard; Daniel F. Hermens; Maxwell R. Bennett; Jim Lagopoulos; Ian B. Hickie (Brain Imaging and Behavior, 2017)

Water depth is a strong driver of intra-lake diatom distributions in a small boreal lake - Cale A. C. Gushulak; Kathleen R. Laird; Joseph R. Bennett; Brian F. Cumming (Journal of Paleolimnology, 2017)

Impact of Fiber Structure on the Material Stability and Rupture Mechanisms of Coronary Atherosclerotic Plaques - Graeham R. Douglas; Adam J. Brown; Jonathan H. Gillard; Martin R. Bennett; Michael P. F. Sutcliffe; Zhongzhao Teng (Annals of Biomedical Engineering, 2017)

Genome-wide association study reveals genetic architecture of coleoptile length in wheat - Genqiao Li; Guihua Bai; Brett F. Carver; Norman C. Elliott; Rebecca S. Bennett; Yanqi Wu; Robert Hunger; J. Michael Bonman; Xiangyang Xu (Theoretical and Applied Genetics, 2017)

Community assembly on isolated islands: macroecology meets evolution - A. J. Rominger; K. R. Goodman; J. Y. Lim; E. E. Armstrong; L. E. Becking; G. M Bennett; M. S. Brewer; D. D. Cotoras; C. P. Ewing; J. Harte; N. D. Martinez; P. M. O'Grady; et al. (Global Ecology and Biogeography, 2016)
Aim Understanding how ecological and evolutionary processes together determine patterns of biodiversity remains a central aim in biology. Guided by ecological theory, we use data from multiple arthropod lineages across the Hawaiian archipelago to explore the interplay between ecological (population dynamics, dispersal, trophic interactions) and evolutionary (genetic structuring, adaptation, speciation, extinction) processes. Our goal is to show how communities develop from the dynamic feedbacks that operate at different temporal and spatial scales. Location The Hawaiian islands (19–22° N , 155–160° W ). Methods We synthesize genetic data from selected arthropods across the Hawaiian archipelago to determine the relative role of dispersal and in situ differentiation across the island chronosequence. From four sites on three high islands with geological ages ranging from Results From the perspective of the island chronosequence we show that species at lower trophic levels develop population genetic structure at smaller temporal and spatial scales than species at higher trophic levels. Network nestedness decreases while modularity increases with habitat age. Single‐island endemics exhibit more specialization than broadly distributed species, but both show the least specialization in communities on middle‐aged substrates. Plant–herbivore networks also show the least deviation from theoretical predictions in middle‐aged communities. Main conclusions The application of ecological theory to island chronosequences can illuminate feedbacks between ecological and evolutionary processes in community assembly. We show how patterns of population genetic structure, decreasing network nestedness, increasing network modularity and increased specialization shift from early assembly driven by immigration, to in situ diversification after > 1 Myr. Herbivore–plant communities only transiently achieve statistical steady state during assembly, presumably due to incomplete assembly from dispersal in the early stages, and the increasing influence of island ontogeny on older islands.

Seasonal Variability in Stormwater Quality Treatment of Permeable Pavements Situated Over Heavy Clay and in a Cold Climate - Ryan J. Winston; Keely M. Davidson-Bennett; Kristen M. Buccier; William F. Hunt (Water, Air, & Soil Pollution, 2016)

Landscape properties mediate the homogenization of bird assemblages during climatic extremes - Angie Haslem; Dale G. Nimmo; James Q. Radford; Andrew F. Bennett (Ecology, 2015)
Extreme weather events, such as drought, have marked impacts on biotic communities. In many regions, a predicted increase in occurrence of such events will be imposed on landscapes already heavily modified by human land use. There is an urgency, therefore, to understand the way in which the effects of such events may be exacerbated, or moderated, by different patterns of landscape change. We used empirical data on woodland‐dependent birds in southeast Australia, collected during and after a severe drought, to document temporal change in the composition of bird assemblages in 24 landscapes (each 100 km 2 ) representing a gradient in the cover of native wooded vegetation (from 60% to and that occurring in productive parts of the landscape, for maintaining bird communities whose composition is resistant to severe drought. While extreme climatic events cannot be prevented, their effects can be ameliorated by managing the pattern of native vegetation in anthropogenic landscapes, with associated benefits for maintaining ecological processes and human well‐being.

Response to: “Comment on: effect of flow confinement on the hydrodynamics of circular impinging jets: implications for erosion assessment” by Spyros Beltaos - Seyed Mohammad Ghaneeizad; Joseph F. Atkinson; Sean J. Bennett (Environmental Fluid Mechanics, 2015)

Optimal fire histories for biodiversity conservation - Luke T. Kelly; Andrew F. Bennett; Michael F. Clarke; Michael A. McCarthy (Conservation Biology, 2015)
Fire is used as a management tool for biodiversity conservation worldwide. A common objective is to avoid population extinctions due to inappropriate fire regimes. However, in many ecosystems, it is unclear what mix of fire histories will achieve this goal. We determined the optimal fire history of a given area for biological conservation with a method that links tools from 3 fields of research: species distribution modeling, composite indices of biodiversity, and decision science. We based our case study on extensive field surveys of birds, reptiles, and mammals in fire‐prone semi‐arid Australia. First, we developed statistical models of species’ responses to fire history. Second, we determined the optimal allocation of successional states in a given area, based on the geometric mean of species relative abundance. Finally, we showed how conservation targets based on this index can be incorporated into a decision‐making framework for fire management. Pyrodiversity per se did not necessarily promote vertebrate biodiversity. Maximizing pyrodiversity by having an even allocation of successional states did not maximize the geometric mean abundance of bird species. Older vegetation was disproportionately important for the conservation of birds, reptiles, and small mammals. Because our method defines fire management objectives based on the habitat requirements of multiple species in the community, it could be used widely to maximize biodiversity in fire‐prone ecosystems. Historiales de Incendios Óptimos para la Conservación de la Biodiversidad

Effect of risk aversion on prioritizing conservation projects - Ayesha I.T. Tulloch; Richard F. Maloney; Liana N. Joseph; Joseph R. Bennett; Martina M.I. Di Fonzo; William J.M. Probert; Shaun M. O'Connor; Jodie P. Densem; Hugh P. Possingham (Conservation Biology, 2015)
Conservation outcomes are uncertain. Agencies making decisions about what threat mitigation actions to take to save which species frequently face the dilemma of whether to invest in actions with high probability of success and guaranteed benefits or to choose projects with a greater risk of failure that might provide higher benefits if they succeed. The answer to this dilemma lies in the decision maker's aversion to risk—their unwillingness to accept uncertain outcomes. Little guidance exists on how risk preferences affect conservation investment priorities. Using a prioritization approach based on cost effectiveness, we compared 2 approaches: a conservative probability threshold approach that excludes investment in projects with a risk of management failure greater than a fixed level, and a variance‐discounting heuristic used in economics that explicitly accounts for risk tolerance and the probabilities of management success and failure. We applied both approaches to prioritizing projects for 700 of New Zealand's threatened species across 8303 management actions. Both decision makers’ risk tolerance and our choice of approach to dealing with risk preferences drove the prioritization solution (i.e., the species selected for management). Use of a probability threshold minimized uncertainty, but more expensive projects were selected than with variance discounting, which maximized expected benefits by selecting the management of species with higher extinction risk and higher conservation value. Explicitly incorporating risk preferences within the decision making process reduced the number of species expected to be safe from extinction because lower risk tolerance resulted in more species being excluded from management, but the approach allowed decision makers to choose a level of acceptable risk that fit with their ability to accommodate failure. We argue for transparency in risk tolerance and recommend that decision makers accept risk in an adaptive management framework to maximize benefits and avoid potential extinctions due to inefficient allocation of limited resources. El Efecto de la Aversión de Riesgo sobre la Priorización de Proyectos de Conservación

Effect of flow confinement on the hydrodynamics of circular impinging jets: implications for erosion assessment - Seyed Mohammad Ghaneeizad; Joseph F. Atkinson; Sean J. Bennett (Environmental Fluid Mechanics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

In contrast to many other mammals, cetaceans have relatively small hippocampi that appear to lack adult neurogenesis - Nina Patzke; Muhammad A. Spocter; Karl Æ. Karlsson; Mads F. Bertelsen; Mark Haagensen; Richard Chawana; Sonja Streicher; Consolate Kaswera; Emmanuel Gilissen; Abdulaziz N. Alagaili; Osama B. Mohammed; Roger L. Reep; et al. (Brain Structure and Function, 2015)

Effects of Antibiotic Physicochemical Properties on Their Release Kinetics from Biodegradable Polymer Microparticles - Sarita R. Shah; Allan M. Henslee; Patrick P. Spicer; Shun Yokota; Sophia Petrichenko; Sachin Allahabadi; George N. Bennett; Mark E. Wong; F. Kurtis Kasper; Antonios G. Mikos (Pharmaceutical Research, 2014)

The potential for indirect effects between co‐flowering plants via shared pollinators depends on resource abundance, accessibility and relatedness - Luísa Gigante Carvalheiro; Jacobus Christiaan Biesmeijer; Gita Benadi; Jochen Fründ; Martina Stang; Ignasi Bartomeus; Christopher N. Kaiser‐Bunbury; Mathilde Baude; Sofia I. F. Gomes; Vincent Merckx; Katherine C. R. Baldock; Andrew T. D. Bennett; et al. (Ecology Letters, 2014)
Co‐flowering plant species commonly share flower visitors, and thus have the potential to influence each other's pollination. In this study we analysed 750 quantitative plant–pollinator networks from 28 studies representing diverse biomes worldwide. We show that the potential for one plant species to influence another indirectly via shared pollinators was greater for plants whose resources were more abundant (higher floral unit number and nectar sugar content) and more accessible. The potential indirect influence was also stronger between phylogenetically closer plant species and was independent of plant geographic origin (native vs. non‐native). The positive effect of nectar sugar content and phylogenetic proximity was much more accentuated for bees than for other groups. Consequently, the impact of these factors depends on the pollination mode of plants, e.g. bee or fly pollinated. Our findings may help predict which plant species have the greatest importance in the functioning of plant–pollination networks.

Turbulence suppression by suspended sediment within a geophysical flow - Sean J. Bennett; Yinting Hou; Joseph F. Atkinson (Environmental Fluid Mechanics, 2014)

Population dynamics of the reef manta ray Manta alfredi in eastern Australia - L. I. E. Couturier; C. L. Dudgeon; K. H. Pollock; F. R. A. Jaine; M. B. Bennett; K. A. Townsend; S. J. Weeks; A. J. Richardson (Coral Reefs, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Hypoxia effects on gill surface area and blood oxygen-carrying capacity of the Atlantic stingray, Dasyatis sabina - Theresa F. Dabruzzi; Wayne A. Bennett (Fish Physiology and Biochemistry, 2013)

A standardised protocol for the validation of banking methodologies for arterial allografts - R. J. Lomas; P. D. F. Dodd; P. Rooney; D. E. Pegg; P. A. Hogg; M. E. Eagle; K. E. Bennett; A. Clarkson; J. N. Kearney (Cell and Tissue Banking, 2013)

Increased competition does not lead to increased phylogenetic overdispersion in a native grassland - Jonathan A. Bennett; Eric G. Lamb; Jocelyn C. Hall; Warren M. Cardinal‐McTeague; James F. Cahill (Ecology Letters, 2013)
That competition is stronger among closely related species and leads to phylogenetic overdispersion is a common assumption in community ecology. However, tests of this assumption are rare and field‐based experiments lacking. We tested the relationship between competition, the degree of relatedness, and overdispersion among plants experimentally and using a field survey in a native grassland. Relatedness did not affect competition, nor was competition associated with phylogenetic overdispersion. Further, there was only weak evidence for increased overdispersion at spatial scales where plants are likely to compete. These results challenge traditional theory, but are consistent with recent theories regarding the mechanisms of plant competition and its potential effect on phylogenetic structure. We suggest that specific conditions related to the form of competition and trait conservatism must be met for competition to cause phylogenetic overdispersion. Consequently, overdispersion as a result of competition is likely to be rare in natural communities.

Diatom-inference models for acid neutralizing capacity and nitrate based on 41 calibration lakes in the Sierra Nevada, California, USA - James O. Sickman; Danuta M. Bennett; Delores M. Lucero; Thomas J. Whitmore; William F. Kenney (Journal of Paleolimnology, 2013)

Fire Mosaics and Reptile Conservation in a Fire‐Prone Region - D. G. NIMMO; L. T. KELLY; L. M. SPENCE‐BAILEY; S. J. WATSON; R. S. TAYLOR; M. F. CLARKE; A. F. BENNETT (Conservation Biology, 2013)
Fire influences the distribution of fauna in terrestrial biomes throughout the world. Use of fire to achieve a mosaic of vegetation in different stages of succession after burning (i.e., patch‐mosaic burning) is a dominant conservation practice in many regions. Despite this, knowledge of how the spatial attributes of vegetation mosaics created by fire affect fauna is extremely scarce, and it is unclear what kind of mosaic land managers should aim to achieve. We selected 28 landscapes (each 12.6 km 2 ) that varied in the spatial extent and diversity of vegetation succession after fire in a 104,000 km 2 area in the semiarid region of southeastern Australia. We surveyed for reptiles at 280 sites nested within the 28 landscapes. The landscape‐level occurrence of 9 of the 22 species modeled was associated with the spatial extent of vegetation age classes created by fire. Biogeographic context and the extent of a vegetation type influenced 7 and 4 species, respectively. No species were associated with the diversity of vegetation ages within a landscape. Negative relations between reptile occurrence and both extent of recently burned vegetation (≤10 years postfire, n = 6) and long unburned vegetation (>35 years postfire, n = 4) suggested that a coarse‐grained mosaic of areas (e.g. >1000 ha) of midsuccessional vegetation (11–35 years postfire) may support the fire‐sensitive reptile species we modeled. This age class coincides with a peak in spinifex cover, a keystone structure for reptiles in semiarid and arid Australia. Maintaining over the long term a coarse‐grained mosaic of large areas of midsuccessional vegetation in mallee ecosystems will need to be balanced against the short‐term negative effects of large fires on many reptile species and a documented preference by species from other taxonomic groups, particularly birds, for older vegetation. Mosaicos de Fuego y la Conservación de Reptiles en una Región Propensa al Fuego

Juvenile Ribbontail Stingray, Taeniura lymma (Forsskål, 1775) (Chondrichthyes, Dasyatidae), demonstrate a unique suite of physiological adaptations to survive hyperthermic nursery conditions - Theresa F. Dabruzzi; Wayne A. Bennett; Jodie L. Rummer; Nann A. Fangue (Hydrobiologia, 2013)

Context dependence in foraging behaviour of Achillea millefolium - Justine D. Karst; Pamela R. Belter; Jonathan A. Bennett; James F. Cahill (Oecologia, 2012)

Predicting the century‐long post‐fire responses of reptiles - Dale. G. Nimmo; Luke T. Kelly; Lisa M. Spence‐Bailey; Simon J. Watson; Angie Haslem; John G. White; Mike F. Clarke; Andrew F. Bennett (Global Ecology and Biogeography, 2012)
Aim We examined the century‐long post‐fire responses of reptiles to (1) determine the time‐scales over which fauna – fire relationships occur, (2) assess the capacity of a conceptual model to predict faunal response to fire, and (3) investigate the degree to which models of fauna – fire relationships can predict species occurrence and are transferable across space. Location A 104,000 km 2 area in the semi‐arid Murray Mallee region of south‐eastern Australia. Methods We surveyed reptiles at 280 sites across a century‐long post‐fire chronosequence. We developed generalized additive mixed models (GAMMs) of the relationship between time since fire and the occurrence of 17 species in two subregions, and compared modelled responses with predictions derived from the conceptual model. The predictive capacity of GAMMs was then assessed (1) within the subregion the model was developed and (2) when transferred into a novel subregion. Results Eleven species displayed a significant relationship with time‐since‐fire, with changes in species probability of occurrence continuing up to 100 years post‐fire. Predictions of the timing of species post‐fire peak in occurrence were accurate for 9 of 13 species models for which a significant fire response was detected, but little success was achieved in predicting the shape of a species' response. GAMMs predicted species occurrence more accurately when applied within the subregion in which they were developed than when transferred into a novel subregion, primarily due to some species responding to fire more strongly in one part of their geographic range. Main conclusions Fire influences the occurrence of reptiles in semi‐arid ecosystems over century‐long time frames. Habitat‐use conceptual models have value in predicting the peak occurrence of species following fire, particularly for species with distributions strongly shaped by fire. Species relationships with fire can differ across their geographic range, probably associated with variation in climatic influences on post‐fire succession and the consequent provision of habitat resources.

Macroscopic to microscopic scales of particle dosimetry: from source to fate in the body - Paul A. Solomon; Peter Gehr; Deborah H. Bennett; Robert F. Phalen; Loyda B. Méndez; Barbara Rothen-Rutishauser; Martin Clift; Christina Brandenberger; Christian Mühlfeld (Air Quality, Atmosphere & Health, 2012)

From the Science to the Application of Connectivity Conservation - Andrew F. Bennett (Conservation Biology, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Wildlife trade products available to U.S. military personnel serving abroad - Heidi E. Kretser; McKenzie F. Johnson; Lisa M. Hickey; Peter Zahler; Elizabeth L. Bennett (Biodiversity and Conservation, 2012)

Biology, ecology and conservation of the Mobulidae - L. I. E. Couturier; A. D. Marshall; F. R. A. Jaine; T. Kashiwagi; S. J. Pierce; K. A. Townsend; S. J. Weeks; M. B. Bennett; A. J. Richardson (Journal of Fish Biology, 2012)
The Mobulidae are zooplanktivorous elasmobranchs comprising two recognized species of manta rays ( Manta spp.) and nine recognized species of devil rays ( Mobula spp.). They are found circumglobally in tropical, subtropical and temperate coastal waters. Although mobulids have been recorded for over 400 years, critical knowledge gaps still compromise the ability to assess the status of these species. On the basis of a review of 263 publications, a comparative synthesis of the biology and ecology of mobulids was conducted to examine their evolution, taxonomy, distribution, population trends, movements and aggregation, reproduction, growth and longevity, feeding, natural mortality and direct and indirect anthropogenic threats. There has been a marked increase in the number of published studies on mobulids since c . 1990, particularly for the genus Manta , although the genus Mobula remains poorly understood. Mobulid species have many common biological characteristics although their ecologies appear to be species‐specific, and sometimes region‐specific. Movement studies suggest that mobulids are highly mobile and have the potential to rapidly travel large distances. Fishing pressure is the major threat to many mobulid populations, with current levels of exploitation in target fisheries unlikely to be sustainable. Advances in the fields of population genetics, acoustic and satellite tracking, and stable‐isotope and fatty‐acid analyses will provide new insights into the biology and ecology of these species. Future research should focus on the uncertain taxonomy of mobulid species, the degree of overlap between their large‐scale movement and human activities such as fisheries and pollution, and the need for management of inter‐jurisdictional fisheries in developing nations to ensure their long‐term sustainability. Closer collaboration among researchers worldwide is necessary to ensure standardized sampling and modelling methodologies to underpin global population estimates and status.

Reproductive biology of Zearaja chilensis (Chondrichthyes: Rajidae) in the south‐east Pacific Ocean - C. Bustamante; C. Vargas‐Caro; M. C. Oddone; F. Concha; H. Flores; J. Lamilla; M. B. Bennett (Journal of Fish Biology, 2012)
Between 2000 and 2002, three artisanal landing sites were sampled in southern Chile, with data on population structure and reproductive development collected from 5477 yellownose skates Zearaja chilensis . Total length ( L T ) ranged from 33 to 158 cm for females and 34 to 155 cm for males. No sexual dimorphism was evident in disc size (length or width) or in L T – mass relationships. The smallest mature female was 95 cm L T and the size at which 50% were mature ( L T50 ) was 109 cm. Males matured between 80 and 90 cm L T with a L T50 of 88 cm. Although the largest Z . chilensis captured by the artisanal fishery was 155 cm L T , 89% of landings comprised relatively small, immature fish. This situation may compromise the stock integrity if intrinsic vulnerability and probable long‐life span of Z . chilensis are considered. Consequences for the survival of the species and possible signs of a fishery collapse must be reviewed by management authorities by consideration of both artisanal and industrial landings in Chile.

Countryside vegetation provides supplementary habitat at the landscape scale for woodland birds in farm mosaics - Angie Haslem; Andrew F. Bennett (Biodiversity and Conservation, 2011)

The relative timing between eye and hand in rapid sequential pointing is affected by time pressure, but not by advance knowledge - F. J. A. Deconinck; V. van Polanen; G. J. P. Savelsbergh; S. J. Bennett (Experimental Brain Research, 2011)

Association of common DNA sequence variants at 33 genetic loci with blood lipids in individuals of African ancestry from Jamaica - R. Gupta; K. Ejebe; J. Butler; G. Lettre; H. Lyon; C. Guiducci; R. Wilks; F. Bennett; T. Forrester; B. Tayo; K. Musunuru; J. Hirschhorn; et al. (Human Genetics, 2010)

Broad‐scale environmental response and niche conservatism in lacustrine diatom communities - Joseph R. Bennett; Brian F. Cumming; Brian K. Ginn; John P. Smol (Global Ecology and Biogeography, 2010)
Aim (1) To resolve theoretical debates regarding the role of environment versus dispersal limitation, the conservatism of niches across distances and the prevalence of environmental specialists in diatom communities. (2) To provide guidance on the use of diatom communities and other microbial analogues to analyse ecological response to environmental change. Location Eight hundred and ninety‐one lakes in five regional datasets from north‐western Europe and four regional datasets from north‐eastern North America. Methods Lacustrine diatom communities were analysed at three scales: inter‐continental, intra‐continental and regional. Nested partial redundancy analyses (RDAs) were used to determine spatial versus environmental components of community variation. Weighted‐averaging (WA) regression and calibration, as well as logistic and quadratic regressions, were used to detect niche conservatism and the prevalence of environmental specialists. Results Community patterns indicate that dispersal limitation acts predominantly at the inter‐continental scale, while at the regional (less than c . 1,000,000 km 2 ) scale, a single environmental variable (pH) explains more than five times the community variation as spatial (dispersal‐related) variables. In addition, pH niche components appear to be conserved at the inter‐continental scale, and environmental specialization does not impose relative rarity, as specialists apparently readily disperse to suitable environments. Main conclusions Analysis at multiple scales is clearly important in determining the influences of community variation. For diatom communities, dispersal limitation acts most strongly at the broadest scales, giving way to environment at the scales considered by most analyses. The availability of a wide variety of propagules with consistent niches across regions indicates that diatom communities reflect the succession of taxa according to local environmental conditions, rather than disequilibrium with the environment or adaptation of local populations. While multi‐scale analyses must be undertaken for other groups to resolve debates over community drivers and determine appropriate scales for prediction, for diatoms (and probably other microbial communities), responses to environmental change can be inferred using analogue datasets from large geographic areas.

Molecular evolution of a Drosophila homolog of human BRCA2 - Sarah M. Bennett; Mohamed A. F. Noor (Genetica, 2009)

Differing responses to landscape change: implications for small mammal assemblages in forest fragments - Greg J. Holland; Andrew F. Bennett (Biodiversity and Conservation, 2009)

Angular momentum synergies during walking - Thomas Robert; Bradford C. Bennett; Shawn D. Russell; Christopher A. Zirker; Mark F. Abel (Experimental Brain Research, 2009)

Cigarette smoking, body mass index, gastro-esophageal reflux disease, and non-steroidal anti-inflammatory drug use and risk of subtypes of esophageal and gastric cancers by P53 overexpression - Jonine D. Figueroa; Mary Beth Terry; Marilie D. Gammon; Thomas L. Vaughan; Harvey A. Risch; Fang-Fang Zhang; David E. Kleiner; William P. Bennett; Christine L. Howe; Robert Dubrow; Susan T. Mayne; Joseph F. Fraumeni; et al. (Cancer Causes & Control, 2009)

Chinese herbal medicine for Mild Cognitive Impairment and Age Associated Memory Impairment: a review of randomised controlled trials - Brian H. May; Angela W. H. Yang; Anthony L. Zhang; Michael D. Owens; Louise Bennett; Richard Head; Lynne Cobiac; Chun Guang Li; Helmut Hugel; David F. Story; Charlie C. L. Xue (Biogerontology, 2009)

Global biogeography and ecology of body size in birds - Valérie A. Olson; Richard G. Davies; C. David L. Orme; Gavin H. Thomas; Shai Meiri; Tim M. Blackburn; Kevin J. Gaston; Ian P. F. Owens; Peter M. Bennett (Ecology Letters, 2009)
In 1847, Karl Bergmann proposed that temperature gradients are the key to understanding geographic variation in the body sizes of warm‐blooded animals. Yet both the geographic patterns of body‐size variation and their underlying mechanisms remain controversial. Here, we conduct the first assemblage‐level global examination of ‘Bergmann’s rule’ within an entire animal class. We generate global maps of avian body size and demonstrate a general pattern of larger body sizes at high latitudes, conforming to Bergmann’s rule. We also show, however, that median body size within assemblages is systematically large on islands and small in species‐rich areas. Similarly, while spatial models show that temperature is the single strongest environmental correlate of body size, there are secondary correlations with resource availability and a strong pattern of decreasing body size with increasing species richness. Finally, our results suggest that geographic patterns of body size are caused both by adaptation within lineages, as invoked by Bergmann, and by taxonomic turnover among lineages. Taken together, these results indicate that while Bergmann’s prediction based on physiological scaling is remarkably accurate, it is far from the full picture. Global patterns of body size in avian assemblages are driven by interactions between the physiological demands of the environment, resource availability, species richness and taxonomic turnover among lineages.

Regional variation in the historical components of global avian species richness - Gavin H. Thomas; C. David L. Orme; Richard G. Davies; Valerie A. Olson; Peter M. Bennett; Kevin J. Gaston; Ian P. F. Owens; Tim M. Blackburn (Global Ecology and Biogeography, 2008)
Aim Using a global data base of the distribution of extant bird species, we examine the evidence for spatial variation in the evolutionary origins of contemporary avian diversity. In particular, we assess the possible role of the timing of mountain uplift in promoting diversification in different regions. Location Global. Methods We mapped the distribution of avian richness at four taxonomic levels on an equal‐area 1° grid. We examined the relationships between richness at successive taxonomic levels (e.g. species richness vs. genus richness). We mapped the residuals from linear regressions of these relationships to identify areas that are exceptional in the number of lower taxa relative to the number of higher taxa. We use generalized least squares models to test the influence of elevation range and temperature on lower‐taxon richness relative to higher‐taxon richness. Results Peaks of species richness in the Neotropics were congruent with patterns of generic richness, whilst peaks in Australia and the Himalayas were congruent with patterns of both genus and family richness. Hotspots in the Afrotropics did not reflect higher‐taxon patterns. Regional differences in the relationship between richness at successive taxonomic levels revealed variation in patterns of taxon co‐occurrence. Species and genus co‐occurrence was positively associated with elevational range across much of the world. Taxon occurrence in the Neotropics was associated with a positive interaction between elevational range and temperature. Conclusions These results demonstrate that contemporary patterns of richness show different associations with higher‐taxon richness in different regions, which implies that the timing of historical effects on these contemporary patterns varies across regions. We suggest that this is due to dispersal limitation and phylogenetic constraints on physiological tolerance limits promoting diversification. We speculate that diversification rates respond to long‐term changes in the Earth's topography, and that the role of tropical mountain ranges is implicated as a correlate of contemporary diversity, and a source of diversification across avian evolutionary history.

Methods for conducting an economic opportunity survey in smallholder dairy farms - K. V. Nordlund; W. J. Goodger; T. B. Bennett; M. Shamsuddin; R. F. Klos (Tropical Animal Health and Production, 2007)

Possible Involvement of Different Connexin43 Domains in Plasma Membrane Permeabilization Induced by Ischemia-Reperfusion - Mauricio A. Retamal; Kurt A. Schalper; Kenji F. Shoji; Juan A. Orellana; Michael V. L. Bennett; Juan C. Sáez (The Journal of Membrane Biology, 2007)

Diazinon Mitigation in Constructed Wetlands: Influence of Vegetation - M. T. Moore; C. M. Cooper; S. Smith; R. F. Cullum; S. S. Knight; M. A. Locke; E. R. Bennett (Water, Air, & Soil Pollution, 2007)

Contaminants in tilapia (Oreochromis mossambicus) from the Salton Sea, California, in relation to human health, piscivorous birds and fish meal production - Marie F. Moreau; Janie Surico-Bennett; Marie Vicario-Fisher; David Crane; Russel Gerads; Richard M. Gersberg; Stuart H. Hurlbert (Hydrobiologia, 2007)

Energy, range dynamics and global species richness patterns: reconciling mid‐domain effects and environmental determinants of avian diversity - David Storch; Richard G. Davies; Samuel Zajíček; C. David L. Orme; Valerie Olson; Gavin H. Thomas; Tzung‐Su Ding; Pamela C. Rasmussen; Robert S. Ridgely; Peter M. Bennett; Tim M. Blackburn; Ian P. F. Owens; et al. (Ecology Letters, 2006)
Spatial patterns of species richness follow climatic and environmental variation, but could reflect random dynamics of species ranges (the mid‐domain effect, MDE). Using data on the global distribution of birds, we compared predictions based on energy availability (actual evapotranspiration, AET, the best single correlate of avian richness) with those of range dynamics models. MDE operating within the global terrestrial area provides a poor prediction of richness variation, but if it operates separately within traditional biogeographic realms, it explains more global variation in richness than AET. The best predictions, however, are given by a model of global range dynamics modulated by AET, such that the probability of a range spreading into an area is proportional to its AET. This model also accurately predicts the latitudinal variation in species richness and variation of species richness both within and between realms, thus representing a compelling mechanism for the major trends in global biodiversity.

The extracellular matrix protein ?IG-H3 is expressed at myotendinous junctions and supports muscle cell adhesion - Jill W. Ferguson; Brian S. Thoma; Michelle F. Mikesh; Randall H. Kramer; Kelly L. Bennett; Anthony Purchio; Bradford J. Bellard; Richard G. LeBaron (Cell and Tissue Research, 2003)

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Comment: Formation and reorientation of structure in the surge‐type glacier Kongsvegen, Svalbard J. Woodward, T. Murray and A. Mc Caig (2002) Journal of Quaternary Science 17 : 201–209 - N. F. Glasser; M. J. Hambrey; M. R. Bennett; D. Huddart (Journal of Quaternary Science, 2003)

Electrophoretic variation as a measure of speciesdifferentiation between four species of the genus Lolium - Sarita Jane Bennett; Mike D. Hayward; Dave F. Marshall (Genetic Resources and Crop Evolution, 2002)

Basis for Intracellular Retention of a Human Mutant of the Retinal Rod Channel a Subunit - N. Mallouk; M. Ildefonse; F. Pag s; M. Ragno; N. Bennett (The Journal of Membrane Biology, 2002)

Discordant patterns of morphological and molecular change in broadtail madtoms (genus Noturus ) - R. Q. Bennetts; J. M. Grady; F. C. Rohde; J. M. Quattro (Molecular Ecology, 1999)
Two morphologically distinct forms of an undescribed madtom catfish ( Noturus sp.) occur in the rivers and lakes of southeastern USA. ‘Lake’ broadtail madtoms are endemic to Lake Waccamaw and are probably related to nearby ‘river’ broadtail populations. To investigate phylogenetic relationships, we surveyed mitochondrial DNA (mtDNA) sequence variation in ‘lake’ and ‘river’ broadtails and other members of the genus Noturus . Mitochondrial rDNA data suggest a sister group relationship between broadtail madtoms and N. insignis , not N. leptacanthus as posited previously. Population‐level analyses using additional mtDNA characters (NADH dehydrogenase subunit 2 (ND2) and cytochrome b (Cyt b )) identified two highly divergent genetic lineages within broadtail madtoms that do not correspond to the morphological designations ‘river’ and ‘lake’.

The reach-to-grasp movement in Parkinson's disease: response to a simultaneous perturbation of object position and object size - U. Castiello; K. Bennett; C. Bonfiglioli; S. Lim; R. F. Peppard (Experimental Brain Research, 1999)

Glacigenic clast fabrics: genetic fingerprint or wishful thinking? - Matthew R. Bennett; Richard I. Waller; Neil F. Glasser; Michael J. Hambrey; David Huddart (Journal of Quaternary Science, 1999)

Interactive effects of subanesthetic ketamine and subhypnotic lorazepam in humans - John H. Krystal; Laurence P. Karper; Alexandre Bennett; D. Cyril D'Souza; Anissa Abi-Dargham; Kristen Morrissey; Danielle Abi-Saab; J. Douglas Bremner; M. B. Bowers Jr.; Raymond F. Suckow; Philip Stetson; George R. Heninger; et al. (Psychopharmacology, 1998)

Zipping up transcription factors: Rational design of anti-Jun and anti-Fos peptides - Naresh P. S. Bains; Jackie A. Wilce; Katja H. Heuer; Mark Tunstall; Joel P. Mackey; Max R. Bennett; Anthony S. Weiss; Glenn F. King (International Journal of Peptide Research and Therapeutics, 1997)

Generalized inversion of a global numerical weather prediction model, II: Analysis and implementation - A. F. Bennett; B. S. Chua; L. M. Leslie (Meteorology and Atmospheric Physics, 1997)

MUC1 gene polymorphism and gastric cancer–an epidemiological study - F Carvalho; R Seruca; L David; A Amorim; M Seixas; E Bennett; H Clausen; M Sobrinho-Simoes (Glycoconjugate Journal, 1997)

Parasite faunas, testosterone and secondary sexual traits in male red-winged blackbirds - Patrick J. Weatherhead; Karen J. Metz; Gordon F. Bennett; Rebecca E. Irwin (Behavioral Ecology and Sociobiology, 1993)

Latency and reactivation of infectious laryngotracheitis vaccine virus - C. S. Hughes; R. A. Williams; R. M. Gaskell; F. T. W. Jordan; J. M. Bradbury; M. Bennett; R. C. Jones (Archives of Virology, 1991)

Studies on poxvirus infection in cats - M. Bennett; R. M. Gaskell; C. J. Gaskell; D. Baxby; D. F. Kelly (Archives of Virology, 1989)

Allorhogas pyralophagus [Hym.: Braconidae], a gregarious external parasite imported into texas, USA, for biological control of the stalkborerEoreuma loftini [Lep.: Pyralidae] on sugar cane - J. W. Smith; H. W. Browning; F. D. Bennett (BioControl, 1987)

Plagiprospherysa trinitatis [Dipt.: Tachinidae], A parasite ofElasmopalpus lignosellus [Lep.: Phycitidae] in Trinidad, W. I. - M. N. Beg; F. D. Bennett (BioControl, 1974)

Biological control ofDiatraea saccharalis (F.) in Barbados byApanteles flavipes Cam. andLixophaga Diatraeae T. T. - M. M. Alam; F. D. Bennett; K. P. Carl (BioControl, 1971)

Current status of biological control of the small moth borers of sugar caneDiatraea spp. [Lep. Pyraeididae] - F. D. Bennett (BioControl, 1971)

Some factors affecting interferon production by foot-and-mouth disease virus in bovine tissue cultures - R. F. Sellers; J. H. Bennett; G. N. Mowat; W. A. Snowdon (Archives of Virology, 1968)

The use of interferon production as a marker in the development of a modified strain of foot-and-mouth disease virus - R. F. Sellers; G. N. Mowat; J. H. Bennett; D. A. Barr (Archives of Virology, 1968)

Biological control ofOpuntia spp. byCactoblastis cactorum in the Leeward Islands (West Indies) - F. J. Simmonds; F. D. Bennett (BioControl, 1966)

The taxonomic status of Lineola longa - John F. Bennett; E. Canale-Parola (Archives of Microbiology, 1965)

The effect of agar on the inhibitory activities of fatty amines - F. J. Hanus; E. O. Bennett (Antonie van Leeuwenhoek, 1964)

Studies on the life history and biological control of the spittlebug,Clastoptera undulata uhler (Cercopidae: Hemiptera) - F. D. Bennett; I. W. Hughes (BioControl, 1963)

Preliminary seed potato certification notes - C. Tice; E. P. Sandsten; E. R. Bennett; F. M. Harrington; H. O. Werner; J. A. Hill (American Journal of Potato Research, 1923)